STUDY OF RESULT AND QUALITY OF MILLED RICE FROM KIND OF NEW SUPERIR RICE VARIETIES - Alif Waluyo (Jurnal Agrivet, 2021)
The findings of superior varieties of early maturing rice, good irrigation facilities supported using production technology allow rice harvesting in Indonesia to be caried out 2 to 3 times a year. The main problem in postharvest handling of rice is the high yield loss and the grain and rice produced are of low quality. The influencing factor is the rice mulling process, based on the rice milling capacity, there are three group namely large, medium and small rice mills (PPB, PPD and PPK), from the three rice mill groups reported the highest yield loss was in the PPK category. The purpose of the study was to calculate the yield and quality of milled rice using PPK equipment/ machines. The factor affects the work of rice milling is the material factor. The result showed that the milling capacity was 8.38 kg/minute, milled yield 65,15 %, percentage of head rice 78,3 %, percentage of broken rice 18.5 %, percentage of groats 4.2 %, and the level of sosoh 88.6 % this is the factor that must be known in order to be able to improve regarding the yield and quality of milled rice.